Seasonal Prevalence Of Gastrointestinal Helminths In Goats - Hafiz, A.; Talukdar , S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Parasitic infections are severe constraints to livestock productivity and cause considerable economic losses. Like other species, goats are also highly susceptible to variety of gastrointestinal parasites. Various factors viz. age, sex, season and agro-climatic conditions are responsible for the prevalence of helminthic infection. Seasonal variation in prevalence or intensity of gastrointestinal parasitic infection in goats has been reported from Nagpur, India (Maske et al., 1990). Hence present study was carried out to assess the occurrence of gastrointestinal helminths in goat during different season under the agroclimatic condition of Assam.